2018
DOI: 10.1016/j.scr.2018.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Generation of patient-specific induced pluripotent stem cells from Leber's hereditary optic neuropathy

Abstract: Leber's hereditary optic neuropathy (LHON) is a maternally inherited mitochondrial disease caused by homoplasmic point mutations in complex I subunit genes of mitochondrial DNA. In this report, we generated an induced pluripotent stem cell (iPSCs) line, TVGH-iPSC-010-09, from the peripheral blood mononuclear cells of a female patient with Leber's hereditary optic neuropathy (LHON) by using the Sendai-virus delivery system. The resulting iPSCs retained the disease-causing mitochondrial DNA mutation, expressed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…hiPSCs were generated from peripheral blood mononuclear cells obtained from a healthy control donor and LHON patient by overexpression of four reprogramming factors, Oct-4, SOX2, c-Myc and KLF4, based on our previously published protocol [18]. RGCs were then differentiated from the generated hiPSCs in a stepwise manner following the protocol adapted from Ohlemacher [19] with several modifications as outlined in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…hiPSCs were generated from peripheral blood mononuclear cells obtained from a healthy control donor and LHON patient by overexpression of four reprogramming factors, Oct-4, SOX2, c-Myc and KLF4, based on our previously published protocol [18]. RGCs were then differentiated from the generated hiPSCs in a stepwise manner following the protocol adapted from Ohlemacher [19] with several modifications as outlined in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
“…Since RGCs appear at the early stage of retina development, it was suggested that RGCs could be isolated from the OVs at 25–30 days after the initiation of differentiation [22]. We have successfully differentiated hiPSCs derived from LHON patients and purified RGCs from the OVs [18,24]. Still, little is known about the pathogenic mechanisms of LHON.…”
Section: Discussionmentioning
confidence: 99%
“…They observed a return of apoptosis to normal levels in the cybrid-corrected RGCs in comparison with the increased levels found in LHON iPSC-derived RGCs [102]. More groups generated iPSC models of LHON with the representative mutation m.11778G>C; p.Arg340His [103,104]. One of them, Wu et al, showed defective neurite outgrowth in RGCs differentiated from patient iPSCs and improved mitochondrial biogenesis as a compensatory mechanism.…”
Section: Potential Applications For Ipsc-derived Rgcsmentioning
confidence: 99%
“…Multiple iPSC lines have been generated from fibroblasts of LHON patients. These lines offer unique opportunities to investigate LHON phenotypes and regulatory mechanisms at the cellular level ( 59 61 ). Unfortunately, the generated cells are not organized as they would be in the retina, which prevents their use in cell therapy.…”
Section: Medical Treatmentmentioning
confidence: 99%